Predictors and Risk Factors of Surgical Site Infection (SSI) Following Adult Spine Surgery: A Cross-sectional Study - Waleed Awwad; Abdullah Alnasser; Abdulrahman Almalki; Rohail Mumtaz; Bander Alsubaie; Abdulaziz Almaawi; Abdulaziz N Aljurayyan; Khalid Alsaleh (Journal of Spine Practice)
Introduction: Surgical site infection (SSI) is a major cause of morbidity and mortality as it is known to increase the length of hospital stay, revision surgery, and re-operation. Identifying patients at risk of developing SSI before surgery is the key to prevent SSI.